A top-down approach in fuzzy controller design with VHDL - Khandaker Abul Kalam Azad,; Zahari Mohamed Darus,; Mohd Alauddin Mohd Ali, (1999)
With the rapid increase in size and complexity of digital systems, hardware description languages, such as VHDL, are quickly becoming the main integral part of the tools used for advanced digital system design. Although many of the HDL-based design practices follow bottom-up fashion, the real strength of VHDL is that it facilitates the top-down design process where high level design concepts can be described and verified without delving into implementation details. The top-down design approach is described in this paper for designing a multi-level fuzzy controller